Innate Immune Sensing of Viruses and Its Consequences for the Central Nervous System - Singh, Hina (Viruses, 2021)
Viral infections remain a global public health concern and cause a severe societal and economic burden. At the organismal level, the innate immune system is essential for the detection of viruses and constitutes the first line of defense. Viral components are sensed by host pattern recognition receptors (PRRs). PRRs can be further classified based on their localization into Toll-like receptors (TLRs), C-type lectin receptors (CLR), retinoic acid-inducible gene-I (RIG-I)-like receptors (RLRs), NOD-like receptors (NLRs) and cytosolic DNA sensors (CDS). TLR and RLR signaling results in production of type I interferons (IFNα and -β) and pro-inflammatory cytokines in a cell-specific manner, whereas NLR signaling leads to the production of interleukin-1 family proteins. On the other hand, CLRs are capable of sensing glycans present in viral pathogens, which can induce phagocytic, endocytic, antimicrobial, and pro- inflammatory responses. Peripheral immune sensing of viruses and the ensuing cytokine response can significantly affect the central nervous system (CNS). But viruses can also directly enter the CNS via a multitude of routes, such as the nasal epithelium, along nerve fibers connecting to the periphery and as cargo of infiltrating infected cells passing through the blood brain barrier, triggering innate immune sensing and cytokine responses directly in the CNS. Here, we review mechanisms of viral immune sensing and currently recognized consequences for the CNS of innate immune responses to viruses.